Bilateral orbital rhabdomyosarcoma mimicking burkitt's lymphoma (1998)
Bilaterial orbital rhabdomyosarcoma mimicking Burkitt's lymphoma in an 11-year old girl is reported. The patient presented with bilateral proptosis and right cervical lymphadenopathy. Despite consultations at a number of hospitals, a definitive diagnosis was not made until presentation at the University College Hospital, Ibadan, where cytological examination of a fine needle aspiration biopsy specimen of the tumour and the lymph node revealed. changes that were consistent with those seen in rhabdomyosarcoma. This case emphasises the fact that rhabdomyosarcoma is an important differential diagnosis of orbital tumours in childhood, especially in Burkitt's lymphoma endemic areas.